THE INFLUENCE OF PYROLYSIS ON THE ENERGY PROPERTIES OF AGRICULTURAL BIOMASS - Matin, Ana; Krička, Tajana; Grubor, Mateja; Jurišić, Vanja; Majdak, Tugomir; Špelić, Karlo; Matin, Božidar; Jovičić, Nives; Antonović, Alan; Brandić, Ivan (Journal on Processing and Energy in Agriculture, 2023)
At the beginning and during the development of civilization, natural sources were the only available source of energy. With the development of society and industry, they were replaced by intensive use of fossil fuels. Non-renewability and negative impact on the environment called into question the rationality of using such sources. Therefore, natural sources of energy are becoming more and more important, especially biomass, which is becoming an important source of energy due to its ecological advantages. There are numerous ways to convert agricultural biomass into different forms of biofuel. Thermochemical conversion includes a process of pyrolysis in which, under the influence of a high temperature of 400 to 600 °C without the presence of oxygen, very valuable products are obtained in the form of biochar. Agricultural biomass of the main agricultural crops (corn, wheat, barley, oats, triticale, rye, soybeans, oilseeds and sunflower) was used for this research. The obtained results show that the pyrolysis process improves its energy properties and that agricultural biomass is very suitable as a raw material for direct combustion. Moreover, the mentioned raw materials are characterized by significant pyrolytic conversion potential, i.e. biochar production ranges from 30.03% to 47.0%. Similarly, the heating value (HHV) of biochar after the pyrolysis process increased to 27.11 MJ/kg, which proves that agricultural biomass is a good source of energy per unit mass.
Keywords: agricultural biomass; pyrolysis; energetic properties; biochar